Positive resonance: Successful interpersonal emotion regulation facilitated relationship closeness by enhanced inter-brain synchronization - Tongtong Zhu; Xiaoxuan Zhang; Luyao Jin; Linzi Wang; Yanmei Wang (NeuroImage)
Interpersonal emotion regulation (IER) refers to the dynamic process where a regulator employs specific strategies to alleviate a target's distress. It remains unclear whether successful IER could facilitate interpersonal relationship closeness (IRC). The present study aimed to explore whether successful IER, based on two typical strategies—cognitive reappraisal (CR) and expressive suppression (ES)—for down-regulating the target's negative emotions, could enhance IRC among friend dyads, and to identify the underlying neural correlates of this process using functional near-infrared spectroscopy system. Seventy-four female dyads (friends) were randomly assigned to one of two strategy groups (CR vs. ES), with one participant as the target and the other as the regulator. Our findings revealed that both strategies have down-regulated the target's negative emotions, however, CR strategy was associated with more successful IER outcomes (more improvement of the targets’ negative emotions; higher IRC) than ES strategy. IER recruited the enhanced interpersonal brain synchronization (IBS) of the prefrontal and temporal areas among friend dyads. CR strategy recruited higher IBS of the above-mentioned brain networks than ES strategy in down-regulating the target's sadness, and the reversed IBS pattern was found in down-regulating the target's anger, inferring that CR was more successive in IER of sadness, and ES was more effective in IER of anger. The increased IBS pattern of these brain regions played a mediational role between the effectiveness of down-regulating targets’ negative emotions and the increment of IRC. Our findings revealed a neural coupling mechanism through which successful IER fostered supportive social bonds.